The feasibility, acceptability and possible benefit of a positive psychology intervention group in an adolescent inpatient eating disorder service. Issue 5 (2nd September 2016) - Harrison, Amy; Al-Khairulla, Hind; Kikoler, Maxim
Abstract : Positive affect focused therapies could increase subjective happiness and life satisfaction for patients with eating disorders (EDs), illnesses known to significantly impact quality of life. This longitudinal pilot study aimed to develop and implement a five session 'Positivity Group' using positive psychology interventions (PPIs) in an adolescent ED inpatient service. Eight female inpatients aged 11–18 years attended the group and subjective happiness and life satisfaction were assessed before, after and at 6-month follow-up. Patients provided feedback on acceptability and feasibility was assessed via patient engagement, facilitator and team feedback and the data support the feasibility and acceptability of the group. A possible benefit was derived from the group, with 75% of patients reporting meaningful improvement in subjective happiness and 87.5% in life satisfaction. Involving the wider team and supporting homework were identified as considerations for future replication alongside the assessment of implementation, acceptability, feasibility and effectiveness in other clinical contexts.